2022
DOI: 10.1002/jlcr.3959
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and automated fluorine‐18 radiolabeling of new PSMA‐617 derivatives with a CuAAC radiosynthetic approach

Abstract: In the last decade, the development of new radiopharmaceuticals for the imaging and therapy of prostate cancer has been a highly active and important area of research, especially focusing on the prostate‐specific membrane antigen (PSMA), an antigen which is upregulated in prostate, as well as in other tumor cells. A large variety of PSMA ligands have been radiolabeled, to date. Among the various derivatives, PSMA‐617 resulted to be one of the most interesting in terms of interaction with the antigen and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 39 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…Melanocortin 1 receptor (MC1R)-targeted peptides were radiolabeled using identical 18 F-labeling techniques to produce [ 18 F]­CCZ01064 and [ 18 F]­CCZ01096 with a high radiochemical purity (>95%) and good molar activity (40.7–66.6 MBq/nmol and 115.5–266.5 MBq/nmol, respectively), for imaging melanoma. , Iannone et al group used the CuAAC reaction for 18 F-labeling of a PSMA-617 peptide-based precursor. The authors presented a fully automated radiolabeling of the precursor, which yielded the necessary tracer with an RCY of 6.1% and an RCP more than 99.9% at an appropriate molar activity (>650 GBq/mol) …”
Section: Radiolabeling Of Targeted Ligand Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanocortin 1 receptor (MC1R)-targeted peptides were radiolabeled using identical 18 F-labeling techniques to produce [ 18 F]­CCZ01064 and [ 18 F]­CCZ01096 with a high radiochemical purity (>95%) and good molar activity (40.7–66.6 MBq/nmol and 115.5–266.5 MBq/nmol, respectively), for imaging melanoma. , Iannone et al group used the CuAAC reaction for 18 F-labeling of a PSMA-617 peptide-based precursor. The authors presented a fully automated radiolabeling of the precursor, which yielded the necessary tracer with an RCY of 6.1% and an RCP more than 99.9% at an appropriate molar activity (>650 GBq/mol) …”
Section: Radiolabeling Of Targeted Ligand Moleculesmentioning
confidence: 99%
“…The authors presented a fully automated radiolabeling of the precursor, which yielded the necessary tracer with an RCY of 6.1% and an RCP more than 99.9% at an appropriate molar activity (>650 GBq/mol). 87 Compared with CuAAC, SPAAC reaction can form a more stable 1,2,3-triazole by the conjugation of cyclooctynes with azides in the absence of Cu (I/II) cations, driven by ring strain from cyclic alkynes including DBCO derivatives [e.g., oxadibenzocyclooctyne (ODIBO) and azadibenzocyclooctyne (ADIBO)] and difluorinated cyclooctyne (DIFO) 48 (Figure 3A), affording fewer byproducts, lower cell toxicity, and higher reaction kinetics. 88 In fact, the radiolabeling protocol involving the incorporation of 18 F/ 68 Ga-labeled scaffolds into clickable tumor-targeted peptides was utilized with high radiochemical yields to radiolabel the RGD peptide, cyclic RGD (cRGD) peptide, mesenchymal-epithelial transition factor (c-Met) binding peptide (cMBP), bombesin (BBN) peptide, apoptosis targeting peptide (ApoPep), dual-targeting α v β 3 integrin and galectin-3 peptide, and integrin α v β 6 -specific peptide in high radiochemical yields.…”
mentioning
confidence: 99%
“…In these scenarios, the CuAAC ligation can be particularly useful, as azide- or alkyne-bearing prosthetic groups can be radiolabeled and then clicked to vectors in a one-pot two-step schema. This approach is especially popular in the synthesis of 18 F-labeled agents, as evidenced by a large library of 18 F-labeled clickable groups that includes [ 18 F]­fluorobenzyl azides, , azide- and alkyne-modified [ 18 F]­fluoropyridines, [ 18 F]­fluoroalkyl azides, , [ 18 F]­fluorocarbohydrate azides, ,, [ 18 F]­fluoropolyoxyethylene azides, ,, 3-[ 18 F]­fluoropropyne, 5-[ 18 F]­fluoropentyne, , ethynyl-4-[ 18 F]­fluorobenzene, and [ 18 F]­AMBF 3 . , In one recent example, Wang et al reported the synthesis of a modular scaffold for combined near-infrared (NIR) fluorescence and PET imaging via the CuAAC-mediated modification of an azide-bearing NIR dye with an 18 F-labeled alkyne . The work of Walker et al provides a particularly fine example of the pros and cons of a two-step, CuAAC-driven approach to radiofluorination (Figure ).…”
Section: The Copper-catalyzed Azide–alkyne Cycloadditionmentioning
confidence: 99%
“…This strategy could be even more valuable in the context of clinical translation, as it goes even further to ensure reproducibility, reliability, and cGMP compliance. Iannone et al, for example, recently reported the fully automated synthesis of an 18 F-labeled variant of PSMA-617 in which both the radiofluorination of an azide-based prosthetic group and its subsequent CuAAC reaction with an alkyne-modified analogue of PSMA-617 were performed on a Trasis AllinOne module (Figure A) . The click reaction was performed using aqueous 0.5 M NH 3 as the solvent and Cu­(SO 4 ) 2 ·5 H 2 O as the catalyst, leading to 80% conversion in only 10 min (92% in 20 min).…”
Section: The Copper-catalyzed Azide–alkyne Cycloadditionmentioning
confidence: 99%
See 1 more Smart Citation